The ecological implications of land use change in the Source Regions of the Yangtze and Yellow Rivers, China - Li Na; Wang Genxu; Liu Guangsheng; Lin Yun; Sun Xiangyang (Regional Environmental Change, 2013)
The alpine ecosystems in permafrost regions are extremely sensitive to climate change. The headwater regions of Yangtze River and Yellow River of the Qinghai-Tibet Plateau are on the permafrost area. Aerial photos of the Source Regions of the Yangtze and Yellow River taken in 1968 and three phases of TM images acquired from 1986, 2000, and 2008 were used to analyze the spatial alterations of the land cover and corresponding effects on the environment guided by landscape ecology theory. Firstly, land cover types were divided into three classes and 11 subclasses. Analysis results revealed the trends and magnitude of the eco-environmental changes in the regions over the past four decades and showed a continuous degradation of grasslands and the extension of desertification and salinization. Secondly, five landscape pattern indices (i.e., NP, MPS, PR, SHEI, CONTAG) commonly used in landscape ecological studies were calculated, and results showed that this region had become more centralized and diversified. Finally, the factors causing the degradation of alpine grasslands were analyzed. The regional climate exhibited a tendency toward significant warming and desiccation with the air temperature increased by 0.03 A degrees C per year and relative stable precipitation over the last 40 years. And the temperature of permafrost in 0-20 cm soil layer obviously raised by 0.2-0.3 A degrees C in the last 40 years. The combined effects of climate warming and permafrost variation were the major drivers for the changes of landscape in alpine ecosystems.